Extending the Vase Life of Vanda Orchid Cut Flowers Using Plasma Technology - Choncharoen Sawangrat; Soraya Ruamrungsri; Dheerawan Boonyawan; Takron Opassuwan; Sa-nguansak Thanapornpoonpong; Suchanuch Jaipinta; Chaiartid Inkham; Kanokwan Panjama (Horticulturae)
Flower senescence during transport is a major concern for exporters, as physiological disorders reduce quality and price. Extending vase life is crucial, and while 1-MCP is widely used, it requires low temperatures and is less effective in disease control. Cold plasma generated by dielectric barrier discharge produces reactive oxygen and nitrogen species (RONS), offering an alternative method for preserving cut flowers. This study compared the effectiveness of cold plasma and 1-MCP treatments on the vase life of Vanda ‘Pachara Blue’ orchids. Flowers were treated with T1 (control at 25 °C), T2 (1-MCP), and T3 (cold plasma). Both 1-MCP and cold plasma significantly reduced ethylene production (26.15 and 25.20 µL C2H4/kg/hr, respectively) and respiration rate (63.92 and 57.44 mg CO2/kg/hr, respectively) compared to the control (40.93 µL C2H4/kg/hr and 118.21 mg CO2/kg/hr). Vase life was extended to 19.33 days in both treatments, an 87.12% increase over the control (10.33 days). Additionally, cold plasma slightly improved water uptake and reduced petal discoloration. These findings indicate that cold plasma is a promising alternative to 1-MCP, offering effective flower preservation without the need for low-temperature conditions and potential additional benefits in floral quality.